ANALYSIS OF REGULATORY AND LEGAL DOCUMENTS GOVERNING PERSONNEL TRAINING IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS IN THE REPUBLIC OF UZBEKISTAN - Sayfiev Isroil Turdiyevich (Bright Mind Publishing, 2026)
This article is intended for instructors of higher education institutions of the Republic of Uzbekistan, sports coaches, students, team coaches, and athletes. The paper systematizes the sequence of physical education classes conducted for students. It also explains the content of the theoretical component of physical education courses — the lecture topics that reveal the role of physical education and sports training in maintaining a healthy lifestyle, the sequence of theoretical issues covered [4], and provides an analysis of the regulatory and legal documents that govern personnel training in the field of sports [1,3].
Keywords: Mathematical-statistical, physiological, economic, intellectual, patriotism, competence, integrative, infrastructure, modernization.